HLA-G Orchestrates the Early Interaction of Human Trophoblasts with the Maternal Niche - Gregori, Silvia; Amodio, Giada; Quattrone, Federica; Panina-Bordignon, Paola (Frontiers in Immunology, 2015)
Extravillous trophoblasts (EVTs) play a central role in educating maternal leukocytes, endometrial stromal and endothelial cells to generate a receptive decidual microenvironment tailored to accept the semi-allogeneic fetus. HLA-G, a non-classical HLA class I molecules endowed with immune-regulatory functions is primarily expressed on EVTs lining the placenta and on the naturally-occurring tolerogenic dendritic cells, named DC-10, that are enriched in the human first trimester decidua. Decidual DC-10 are involved in HLA-G-mediated tolerance at the maternal-fetal interface via the secretion of IL-10. EVTs can not only establish a tolerogenic microenvironement through the interaction with maternal innate and adaptive cells but also orchestrates placenta vascular and tissue remodeling, leading to a successful pregnancy. Here, we discuss the potential implications of the HLA-G-mediated cross-talk among the cells present at the maternal-fetal interface, and its role in maintaining a positive relationship between the mother and the fetus.